Analisis Digital Marketing Pada UMKM (Usaha Mikro Kecil Menengah) Rumah Komunitas - Kania, Kania; Prastian, Angga Nadiyanto (BUDGETING : Journal of Business, Management and Accounting, 2024)
Rumah Komunitas's use of digital marketing has opened up opportunities for their growth in the digitalization era. Through a digital marketing strategy that focuses on the website and various social media platforms such as Facebook, TikTok, Youtube, Instagram, and Whatsapp, Rumah Komunitas has managed to expand their reach and increase sales of their products. However, better sales results occurred through the website than through e-commerce platforms such as Shopee and Tokopedia. This research uses a qualitative method with a case study approach to dig deeper into the optimization of digital marketing in increasing sales on the Shopee platform. The data collection techniques used include observation, interviews, and documentation. This research was conducted to identify factors that influence the performance of digital marketing at Rumah Komunitas, especially with a focus on comparing the website and the Shopee platform. The results of the data analysis show that the website is superior in product sales due to its attractive store display, complete product descriptions, and ease of ordering process compared to the Shopee platform. This research provides insight into how Rumah Komunitas can improve their digital marketing effectiveness, especially on the Shopee e- commerce platform, to support their business growth and success in this digital era. Keywords: Digital Marketing, Shopee, Website.